Habitus and Hope: The Function of Early Christian Ritual Practice - Lorencin, Igor (Biblical interpretation, 2025)
This contribution starts with the controversy regarding the problem of the delay of the Parousia in early Christianity and asks which processes have continually renewed and strengthened hope of Christ-followers for the future. In the early Christian ritual participation, the habitus of those involved was shaped. An identity is embodied though mimesis, which contributes toward forming values and norms of a group. In the main part of this investigation, with the help of a socio-cognitive approach, the ritual of the Eucharist is explored within early Christian literature from the New Testament times for the purpose of investigating the embodiment of eschatological hope. In the ritual process, hope about the future is ritualized through repetition, embodiment, and experienced emotions. Continual ritual participation strengthens future hope, so an active Parousia expectation is regularly confirmed and can in such a way be transmitted from one generation to the next.